Strengthening Religious Character through Blended Learning in Islamic Education: A Case Study at Muhammadiyah 16 Surabaya - Veronica, Maria Elen; Mu’ammar, Muhammad Arfan; Shafwan, Muhammad Hambal; Mohamed, Sheik (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose – This study describes the strategies for strengthening religious character through Blended Learning in the subject of Al-Islam and Kemuhammadiyahan, as well as the supporting and inhibiting factors that influence the reinforcement of students' religious character in the teaching of Al-Islam and Kemuhammadiyahan.Methods – This study employed a qualitative method with data collection techniques including interviews, observations, and documentation. Data condensation was applied by interpreting the collected data to derive meaning, from which conclusions could be drawn.Findings – The results showed that the school had implemented various strategies, including the formation of a special team to prevent bullying. The implementation of anti-bullying programs through learning activities, and cooperation with external parties such as the health department and the police. In addition, the programs such as anti-bullying chants and claps, as well as the implementation of the Pancasila Student Profile Strengthening Project (P5), have proven effective in instilling positive values and creating an inclusive school culture. Limitations – This research is limited to literature studies and field data obtained from a single school context.Value – This study recommends strengthening anti-bullying policies through deeper curriculum integration, enhanced teacher training, and increased parental involvement to foster a safer and more supportive educational environment for students.